Peran Profitabilitas dalam Memoderasi Pengaruh Struktur Modal dalam Memediasi Hubungan Likuiditas terhadap Nilai Perusahaan pada Perusahaan Sektor Perdagangan Ritel Periode 2014-2023 - Rafi Ilyas Ramadhan; Bambang Mahmudi; Ika Utami Widyaningsih (Owner : Riset dan Jurnal Akuntansi, 2026)
The purpose of this study is to investigate and prove how liquidity affects company value with capital structure as an intervening variable and profitability as a moderating variable in retail trading sector companies listed on the Indonesian Stock Exchange for the period 2014-2023. The sampling technique used was purposive sampling, yielding 10 companies as samples with 100 data observations. The statistical analysis tools used were IBM SPSS version 30 and Hayes Process, with analysis stages ranging from descriptive statistics to conditional process analysis. The research results indicate that: (1) Liquidity has a positive and significant effect on firm value. (2) Liquidity has a negative and significant effect on capital structure. (3) Capital structure has a positive and significant effect on firm value. (4) Capital structure is able to mediate negatively and significantly the relationship between liquidity and firm value. (5) Profitability moderates the influence of the relationship between capital structure and firm value, with a positive and significant moderating effect. (6) Profitability moderates the indirect effect of liquidity on firm value through capital structure, with a negative and significant moderating effect